Clinical complications and their management in a child with ataxia‐telangiectasia (A‐T): A case report study - Marzieh Heidarzadeh Arani; Reza ArefNezhad; Javad Fathgharib; Asghar Aghamohammadi; Hossein Motedayyen (Clinical Case Reports, 2021)
Abstract Ataxia‐telangiectasia (A‐T) is known as an uncommon autosomal recessive disorder associated with recurrent infections and other clinical complications. The management of its complications can improve life quality of patients.